2019
DOI: 10.1071/cp19076
|View full text |Cite
|
Sign up to set email alerts
|

Associative diazotrophic bacteria from forage grasses in the Brazilian semi-arid region are effective plant growth promoters

Abstract: The study of plant growth-promoting bacteria (PGPB) can identify outstanding bacteria for crops. For forage grasses adapted to drylands, the selection of PGPB can increase the field performance of pastures. The aim of this study was to isolate, and characterise at molecular, biochemical and symbiotic levels, diazotrophic bacteria obtained from buffel grass (Cenchrus ciliaris), sorghum (Sorghum bicolor) and Tifton 85 (Cynodon spp.) from Brazilian semi-arid region fields. Field-grown plants were collected, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
13
0
2
Order By: Relevance
“…Significant effects of water restriction on sesame were observed with a reduction in shoot dry mass, plant height, number of capsules per plant, and sesame productivity from the thirtieth day after planting [ 38 ]. ESA 13 already proved to be an efficient plant growth promoter for rice ( Oryza sativa ) [ 6 ], while ESA 402 showed positive effects on sorghum under full irrigation [ 40 ] and water deprivation conditions [ 7 ]. The results observed for the sesame genotypes in the present study agree with the potential of both bacilli to compose multi-crop inoculants for drylands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant effects of water restriction on sesame were observed with a reduction in shoot dry mass, plant height, number of capsules per plant, and sesame productivity from the thirtieth day after planting [ 38 ]. ESA 13 already proved to be an efficient plant growth promoter for rice ( Oryza sativa ) [ 6 ], while ESA 402 showed positive effects on sorghum under full irrigation [ 40 ] and water deprivation conditions [ 7 ]. The results observed for the sesame genotypes in the present study agree with the potential of both bacilli to compose multi-crop inoculants for drylands.…”
Section: Resultsmentioning
confidence: 99%
“…The Bacillus spp. strains ESA 13 [ 6 ], ESA 402 [ 7 , 40 ], and ESA 441 [ 68 ] were obtained from the “Coleção de Culturas de Micro-organismos de Interesse Agrícola da Embrapa Semiárido” (Embrapa Semiárido, Petrolina-PE, Brazil). They were streaked in LB solid medium (Luria Bertani) and incubated for 24 h at 28 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Sorghum, similar to other Poaceae species, may associate with several diazotrophic bacteria, mainly the genera Azospirillum (Puri et al 2017), Herbaspirillum (Monteiro et al 2012), Gluconacetobacter (Yoon et al 2016), Burkholderia (Silva et al 2018), Stenotrophomonas, Bacillus (Antunes et al 2019) and Bradyrhizobium (Hara et al 2019), which are capable of introducing atmospheric N 2 via biological nitrogen fixation (BNF). Many reports of effective BNF in Poaceae species have been published in the last decade (Morais et al 2012;Baptista et al 2014;Alves et al 2015) but other studies could not find evidence of N 2 fixation in the same Poaceae species (Biggs et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A similar situation of increased Flavobacterium , Aeromonas , Citrobacter , Pseudochrobactrum and Stenotrophomonas abundances after fertilizer input reduction with partial organic material substitution was also observed. Previous studies reported that Flavobacterium , Citrobacter and Stenotrophomonas degrade organic matter, are involved in N cycling (such as promoting nutrient cycling and enhancing soil N) and are enriched when organic materials were introduced into the soil [ 45 , 80 , 81 , 82 ], which explained their higher abundances in treatments with continuous C input (2/4 CN + 2/4 MN and 2/4 CN + 2/4 SN) in this study. A higher C/N ratio in the input fertilizer was selected for bacterial assemblage according to the ecological function and adaptation to the surrounding environment [ 83 ].…”
Section: Discussionmentioning
confidence: 52%